Theoretical Reflections on AGILE DEVELOPMENT METHODOLOGIES. - Nerur, Sridhar; Balijepally, VenuGopal (Communications of the ACM, 2007)
The article discusses agile development methodologies in computer software development. The traditional focus of software design management is shifting from one of optimization and control to one of learning and innovation, which will potentially result in the creation of innovative software that allows users more flexibility than ever before. The authors identify the theoretical and conceptual support for agile development methodologies, while examining the difference in the approaches and their potential effects on the industry.